Estratégias conversacionais em Lua Nua, de Leilah Assumpção: a interação e os conflitos de uma relação conjugal - Artur, Catia Regina Ribeiro (2015)
Literary texts usually try to meet the readers expectations structures, which refers to the type of language used in dialogue, allowing the analysis of oral marks and conversational strategies that are part of the linguistic reality inside. This study aims to examine the conversational strategies used by the characters of the play Moon Naked, by Leilah of Assumption, which facilitate the interaction processes and the achievement of communication goals of the participants. For this purpose, it will seek to check the starting purposes of the characters and the conversational strategies chosen to develop them; monitor the management of production or reception of elocutions during the conversation; observing the projection of "I" and the alignment of participants in interaction to maintain self-image; and analyzing the results of the strategies employed throughout the conversation. The main theoretical frameworks that underlie the analysis are: the theory of "Analysis of Literary Conversation" developed by Preti (2004), concepts of the frame, footing and face proposed by Goffman (1989, 2002, 2012) and the study of interactional control by Fairclough (2001). The research results indicated that the repertoire of conversational strategies of each participant made possible them to deal with a conflict situation, but the self-defense capability and aplomb was decisive so that one of them was more successful in their purpose on this occasion